EVALUATION OF NURSES/MIDWIVES KNOWLEDGE REGARDING POSTPARTUM HEMORRHAGE BEFORE AND AFTER IMPLEMENTATION OF AN EDUCATIONAL PROGRAM AT MATERNITY TEACHING HOSPITAL IN SULAIMANI CITY - Abdulaziz, Tebin Jihan; Mohammed, Atiya Kareem (Journal of Sulaimani Medical College, 2024)
Background The main preventable cause of maternal death and illness worldwide remains postpartum hemorrhage, an obstetric emergency related to vaginal birth and cesarean section. Objectives This study aimed to evaluate the knowledge of nurses and midwives on postpartum hemorrhage before and after an educational program was implemented. Materials and Methods Sixty nurses and midwives who worked in the delivery room and postpartum ward at a maternity teaching hospital in Sulaimani, Iraq, participated in a quasi-experimental study. Results The majority of the participants, 76.7% of Nurses/Midwives, had inadequate knowledge regarding PPH in the pretest, and 68.3% had good knowledge in the posttest. There are statistically significant differences between the pretest & posttest in Knowledge PPH (χ^2= 87.758, p-value=0.000). Conclusion The majority of nurses and midwives had poor knowledge of PPH before the implementation of the educational program, but after being exposed to it, their knowledge significantly increased.
Keywords: Postpartum hemorrhage; NursesMidwives knowledge related to PPH; active management of thethird stage of labor